WORLD PHENOMENA IN CONTEXT OF SOCIAL INTERACTION OF COMMUNITY - Indra Permana; Aditya Permana; Dida Firmansyah (JLER (Journal of Language Education Research), 2018)
The phenomenon of bilingual, especially for the people of Indonesia is common. This is influenced by presence factor L1 and L2 or first language (mother) and second language. Bilingual exists in every country in the world, there are also in every society and all age groups. Based on the way it occurs, bilingualism can be distinguished into the natural bilingualism of natural bilingualism or primary bilingualism and secondary bilingualism secondary boldness. Natural bravery takes place without specific training, while secondary biology occurs through the teaching of a second language that is designed and implemented systematically. Based on the concepts of bilingual that have been mentioned above, in this study, the authors formulate that bilingualism is the habit of the use of two languages in everyday life. The existence of the ability of the two languages, making a person has an option in using the language. Furthermore, the view held is a minimalist view.